Top-Down and Bottom-Up Effects Deployed by a Nurse Shrub Allow Facilitating an Endemic Mediterranean Orchid - Baldelomar, Mariela; Atala, Cristian; Molina-Montenegro, Marco A. (Frontiers in Ecology and Evolution, 2019)
Background Patterns of positive associations between seedlings of one species and sheltering adults of another species are known as the "nurse-plant syndrome". This spatial, positive association is specie-specific and can have direct top-down (canopy) or bottom-up (soil) effects as well as indirect effects like higher tolerance against herbivory. The main objective of our study was to determine the positive interaction between the endemic Chilean orchid Bipinnula fimbriata and the nurse shrub Baccharis macraei in the Mediterranean ecosystem of Chile. Methods To assess the direct and indirect effects of the nurse, we conducted field and greenhouse experiments, respectively. In the field, we performed manipulative experiments assessing the nurse canopy and soil direct effects on the orchid. We measured microclimatic and edaphic variables within and outside nurses, and assessed survival, growth and photochemical efficiency (Fv/Fm) of the orchids. In the greenhouse, we performed experiments assessing the indirect effect of tolerance to simulated herbivory in orchids under nurse and open spaces conditions. We measured survival, flowering percentage, Fv/Fm, total biomass and jasmonic acid of the orchids. Results We found more soil moisture and nutrients under the nurses, and higher photosynthetically active radiation, soil and air temperature in open spaces. Survival, growth and Fv/Fm were significantly higher in plants under the nurses, showing the top-down effect more importance than the bottom-up effect. In the greenhouse experiment, we found higher survival, Fv/Fm, flowering and biomass in orchids under the nurse treatment, independently of the imposed herbivory. Jasmonic acid was significantly higher in those individuals with herbivory and open spaces condition. Conclusions We conclude that B. macraei acts as a nurse for B. fimbriata improving microclimatic and edaphic conditions that result in an increased fitness, physiological status and tolerance against herbivory in the orchids, enhancing their probability of establishment and spread in the Mediterranean Chilean region.